L’enluminure chartraine au XIIe siècle: le légendier illustré de la cathédrale - Rabel, Claudia (Scrineum, 2020)
A Legendary, formerly in the cathedral chapter library of Chartres, ms. 500, stood out amongst the manuscripts burnt in 1944. It was a large volume from the mid-12th century, richly illuminated with an exceptional cycle of 55 historiated initials. Thanks to the recovered fragments and pre-war reproductions and descriptions, the sanctoral and its iconography can be examined in relation with the liturgy, relics and the 13th-century stained-glasses in the Chartres cathedral. The early and rare hagiographical scenes raise a question of their possible Byzantine source of inspiration.